A boosted multi-HMM classifier for recognition of visual speech elements - Foo, Say Wei (2009)
A novel boosted classifier using multiple Hidden Markov Models (HMMs) is reported in this paper. The composite HMMs are specially trained to highlight certain group of training samples with the application of